Connexin 43: A novel ginsenoside Rg1-sensitive target in a rat model of depression. (15th June 2020) - Xia, Cong-Yuan; Wang, Zhen-Zhen; Wang, Hui-Qin; Ren, Si-Yu; Lou, Yu-Xia; Jin, Can; Qu, Tian-Ge; Feng, Si-Tong; Zhang, Yi; Chu, Shi-Feng; Chen, Nai-Hong
Abstract: Our previous studies have shown that ginsenoside Rg1 (Rg1) exerts antidepressant-like effects in animal models of depression, accompanied by an improvement of astrocytic gap junction functions. However, whether connexin 43 (Cx43), the major connexin forming gap junctions between astrocytes, is the key regulator of Rg1-induced antidepressant-like effects is still unknown. In this study, we examine in vitro and in vivo the involvement of Cx43 in the antidepressant effects of Rg1. Corticosterone was used to establish an in vitro rat model of depression. Treatment with Rg1 1 h prior to corticosterone significantly improved the cell viability of astrocytes, which was significantly inhibited by carbenoxolone, a widely used gap junction inhibitor. Moreover, Rg1 treatment significantly ameliorated antidepressant-sensitive behaviours induced by infusion of carbenoxolone or Gap26, a selective inhibitor of Cx43, into the prefrontal cortex of the animals. Rg1 treatment increased the expression of Cx43 compared with Gap26 group. According to these results, the antidepressant-like effects of Rg1 were mainly mediated by Cx43-formed gap junctions. Highlights: Ginsenoside Rg1 protected astrocytes against corticosterone in vitro. None-selective gap junction inhibitor carbenoxolone blocked the protective role of ginsenoside Rg1 against corticosterone in vitro. Ginsenoside Rg1 reversed carbenoxolone- or Gap26-induced antidepressant-sensitive behaviours.